Toxicity Assessment of Sub Lethal Doses of Chlorpyrifos on the Kidney and Liver Organs of Male Wistar Rats (2017)
Chlorpyrifos, an organophosphate pesticide is an important neurotoxic and tissue damage agent. It is one of the most heavily used pesticides in domestic and agricultural applications globally. Repeated doses of chlorpyrifos have been able to cause significant disturbances on the biochemical and physiological functions of the blood, and histological abnormalities in livers and kidneys exposed to this insecticide. The toxicities of sub lethal oral administration of chlorpyrifos daily for 28 days were assessed using a completely randomized design. Twenty-five albino Wistar rats weighing between 150-200 g divided into five groups containing five rats each were housed in the Central Animal house of College of Medicine, University of Ibadan. Chlorpyrifos at 0 (control), 18.9, 25.9, 32.2 and 39.2 mg/kg were orally administered to male rats, respectively for four weeks, between the months of May and June, 2014. At the end of the experimental period, the toxicities of chlorpyrifos were assessed in rats using haematology, serum liver enzymes and histopathological assays. Results revealed significant reduction in body weights compared to control. The packed cell volume (PCV), hemoglobin (Hb) and lymphocytes (Lymp) also showed significant reduction at 39.2, 25.9 and 32.2 mg/kg (39.33, 45.40 and 44.80%), respectively compared to control (49.67%). Insecticide administration to rats resulted in significant elevation of serum transaminases (AST and ALT) and alkaline phosphatase (ALP) from 32.2, 39.2 and 25.9 mg/kg dosages, (ranged from 294.94-542.00 u/L for AST and from 96.25-130.77 u/L for ALT), respectively. Also, experimental treated groups exhibited marked of total protein and altered albumin and globulin contents compared to control. Studies revealed dose dependent increase of histopathological alterations. The livers showed moderate vacuolar change of hepatocytes, having a finely reticulated cytoplasmic and congestion of central veins. The kidneys showed mild focal sloughing off of tubular epithelium of renal cortex, fluid in tubular lumen, tubules appearing dilated and cystic (nephrosis) and proteinaeceous fluid in Bowman's capsule and compressing the glomerulus tufts (Esinophilic). Different concentrations of chlorpyrifos including the lowest tested dose produced marked alterations in the exposed animals in this study and thereby affecting the overall performance in terms of health and wellbeing. Thus, this could cause similar health and environmental risks to humans even at the lowest dose.